Teologi Kapitalistik : Catatan atas Cara Pandang Masyarakat Modern Terhadap Agama - Khoirul Faizin (Universitas Darussalam Gontor, 2011)
As a cultural movement, globalization has presented the differences that tear do wn the totality and unity of values and beliefs .Global culture is characterized by the integration of local culture into the global order. Accordingly ,various foreign cultural values become the bases of the formation of sub-culture that stands alone with the freedom of expression. As a cultural movement, it brings the differences that under mine the totality and the unity of values and religious beliefs. This climate conduci ve to these different ways of life and then spawns a widespread individualization process, which turns man away from the general context. This massive shift can be seen in the so-called “privatization of religion”, the process of individualization in the appreciation and religious practices. Revitalization of religion is needed to restore the basic values of religion that have been secularized. Religion must come back as a legitimate sovereign social values and piety . This sovereignty of religion should be structured as a strategy for revitalizing religion in the lives of individuals and social piety . Thus,religion as a sovereign authority regulates individual piety personally and socially .However, the sovereignty of religion should give a wide freedom for individuals to perform the function of religion in accordance with the present context.